Palimpsesto (2020)
The project's intent is to read the city, the territory and the urban sprawl phenomenon as overlapping architectural languages that continuously rewrite each other leaving behind remnants from the past, in other words a palimpsest. Thus, the architectural proposal aims to be an additional language that can adapt to continuous changes and may lead to the artificial growth of water bodies.